Analisis Perhitungan Pembagian Sisa Hasil Usaha (SHU) Anggota Pada Koperasi Simpan Pinjam Sentosa Samarinda Periode 2016-2017 - Andi Indrawati3, Melita Yuliati Mardiana 2 (EKONOMIA, 2021)
Analisis Perhitungan Pembagian Sisa Hasil Usaha (SHU) Anggota Pada Koperasi Simpan Pinjam Sentosa Samarinda Periode 2016-2017, under guidance of Ms. Mardiana as mentorÂ I and Ms. Andi Indrawati as mentors II.Indonesian continues to development. Cooperatives have a role in weak economic development aims to prioritize the welfare of members by distributing each remaining result of operations (SHU). The greater the member transactions the greater the remaining results of the business (SHU) to be received by the memberThe purpose achieved from this research is to analyze the distribution of residual income result of members business at Koperasi Simpan Pinjam Sentosa Samarinda Period 2016-2017.In order to be elaborated an analysis by using the rule of Undang-Undang Republic Indonesia 1945 Number 25 about Pengkoperasian article 45 which reads about (SHU) in accordance or not with that run by Koperasi Simpan Pinjam Sentosa Samarinda and hypothesis testing. The hyphotesis is accepted because the share of the business result (SHU) of members of the 2017 period increased from 2016.Koperasi Simpan Pinjam Sentosa Samarinda have financial reports such as balanced sheet reports, cash flows and calculation of cooperative funding details for one book years. The lending and borrowing effect to income of Koperasi Simpan Pinjam Sentosa Samarinda is influenced by the participating storage dividen by 40% and the business particapation deviden by 60%. The conclusion of the content of this thesis is the rest of the business results (SHU) members of the period of 2017 increased compared to 2016. In 2016 the cooperative obtained the rest of the business (SHU) of Rp. 19,350,000 then divided from 40% storage participation of Rp. 7,740,000 and divided from 60% business participation of Rp. 11,610,000. Meanwhile, in 2017 the cooperative obtained the remaining operating income (SHU) of members of Rp. 20,250,000 is then divided from the participation of 40% deposit amounting to Rp 8,100,000 and divided by 60% business participation of Rp. 12,150,000.